(3GdJShjb GdTHcj aj ejRGf GdGbJUGO GdESdGej (B:s (3NUGFU GdJShjb GdTHcj(B-(3GdHjY GdeHGTQ(B-(3GdJShjb dbGA YehdGJ GMJeGdjI(B-(3GdJShjb HGdeOjM(B-(3GdHjY GdTLQj(B-(3GdKef hGdYehdGJ(B-(3TQhW GdKef GdJcjja GdTQYj hMceg ddJShjb(B-(3bQGQGJ haJGhi ddJShjb GdTHcj (B/s - (3YjO, YGOd YHO GdaVjd,s 1969- ((3GdEScfOQjI, eUQ (B:s (3OGQ GdJYdje GdLGeYj ddWHGYI hGdfTQ hGdJhRjY,s, 2023)
(3jJfGhd cJGH (B((3GdJShjb GdTHcj aj ejRGf GdGbJUGO GdESdGej(B) (3hGdPj bGe HJCdjag (B((3YGOd YHO GdaVjd YjO(B) (3hjbY aj MhGdj (B(355) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdJShjb YHQ GdEfJQfJ aj GdGbJUGO GdESdGej(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3eGgjI GdJShjb GdTHcj hJejjRg Yf ZjQg, GdaUd GdKGfj (B: (3eMd YbO GdJShjb GdTHcj, GdaUd GdKGdK (B: (3GdJcjja GdTQYj ddJShjb GdTHcj hMceg, GdNGJeI (B: (3GdfJGFL hGdJhUjGJ, GdedGMb(B.s
(3edGMb (B: (3UaMI (B317-341.s
(3jTJed Ydi HHdjhLQGajI(B.s
Keywords: (3GdJShjb YHQ GdEfJQfJ (B((3GbJUGO ESdGej(B)s; (3GdHjY (B((3abg ESdGej(B)s; (3YbhO GdHjY (B((3abg ESdGej(B)s; (3GdJShjb YHQ GdEfJQfJ (B((3abg ESdGej(B)s; (3GdJLGQI GdEdcJQhfjI (B((3GbJUGO ESdGej(B)s; (3GdJLGQI GdEdcJQhfjI (B((3abg ESdGej(B)s; (3GdGbJUGO GdESdGejs